A pleiotropic effect of the APOE gene: association of APOE polymorphisms with multibacillary leprosy in Han Chinese from Southwest China. (13th February 2018) - Wang, D.; Zhang, D.‐F.; Li, G.‐D.; Bi, R.; Fan, Y.; Wu, Y.; Yu, X.‐F.; Long, H.; Li, Y.‐Y.; Yao, Y.‐G.
Summary: Background: Patients with leprosy have a very low risk of Alzheimer disease (AD) and β‐amyloid (Aβ) deposition is significantly lower in the brain tissue of elderly patients with leprosy compared with age‐matched controls. Apolipoprotein E (ApoE) plays a critical role in lipid metabolic pathways and in the brain, facilitating the proteolytic clearance of Aβ. We hypothesized that APOE confers risk of leprosy as lipid metabolism is involved in Mycobacterium leprae infection. Objectives: To investigate the potential genetic associations between APOE and leprosy in two independent Chinese case–control cohorts from the Yuxi and Wenshan prefectures, Yunnan Province of Southwest China. Methods: Five APOE single‐nucleotide polymorphisms (SNPs) were analysed in 1110 individuals (527 patients and 583 controls) from the Yuxi prefecture using a SNaPshot assay. Genetic variations in the entire APOE exons were screened in 1788 individuals (798 patients and 990 controls) from the Wenshan prefecture using next‐generation sequencing technology. Results: The AD‐associated SNPs rs405509 and rs439401 increased the risk of leprosy per se and multibacillary leprosy ( P < 0·005), but the APOE ‐ε4 allele did not. The SNPs rs405509 and rs439401 were cis expression quantitative trait loci (eQTL) for APOE expression in human skin. Differential APOE mRNA expression was observed in skin lesions of patients with type I reaction leprosy and those with multibacillary leprosy. APOE and related lipid genes are involved in an interaction network with leprosy susceptibility genes. Conclusions: The APOE gene is associated with leprosy, most likely by regulating lipid‐metabolism‐related genes. Abstract : What's already known about this topic? Host genetic factors could influence susceptibility to leprosy, which is a chronic infectious and neurological disease. Previous studies have reported a significantly lower level of β‐amyloid (Aβ) deposition in the brain tissues of elderly people with leprosy compared with age‐matched controls. Apolipoprotein E (ApoE) facilitates proteolytic clearance and homeostasis of Aβ peptides in the brain. What does this study add? Common variants of APOE were associated with multibacillary leprosy in Han Chinese. The risk single‐nucleotide polymorphisms rs405509 and rs439401 were cis expression quantitative trait loci for APOE expression in human skin. ApoE may interact with proteins that are coded as leprosy‐risk genes. What is the translational message? Our findings suggested that APOE is associated with leprosy, and this might be mediated by the altered expression of APOE and its potential role in lipid metabolic pathways during Mycobacterium leprae infection. Future studies that explore the potential function of APOE during leprosy onset may offer a novel therapeutic target in leprosy. Linked Article: Morgado de Abreu et al. Br J Dermatol 2018; 178 :833–834 Plain language summary available online Respond to this article